The Role of Interferon–Tau (Ifn–τ) in The Reproduction Handling of Female Ruminant - Sulaiman Ngongu Depamede (Indonesian Center for Animal Research and Development, 2009)
In ruminants, interferon-tau (IFN–τ) is well known as an important pregnancy factor. Interferon-tau as antiluteolytic cytokine is secreted from the tropoblast during the time of implantation. About 10 – 15% of pregnancy losses in cows were possibly due to the lack of IFN–τ to maintain corpus luteum. Interferon-tau induces some early pregnancy factors which are expressed around 15 days post insemination. This has led that IFN–τ to be a strong candidate for the development of ruminant early pregnancy tests. The aim of this paper is to review the existing literatures on the roles of IFN–τ in biology reproduction as well as researches that have been carried out on reproductive biotechnology especially in regards to the development of early pregnancy test for ruminant. It can be concluded that administration of IFN–τ is able to improve reproductive performance of female ruminants experimentally. Interferon-tau and its derivates can be used to develop a rapid test for early pregnancy diagnostic. Key words: Interferon-tau, early pregnancy test, ruminant